2016
DOI: 10.7324/japs.2016.60412
|View full text |Cite
|
Sign up to set email alerts
|

High Doses of PDE5 inhibitors and tramadol reversibly alters haematological parameters in rats

Abstract: This study examined the effect of chronic administration of PDE5 inhibitors and tramadol on haematological indices because of their reported high incidence of abuse. Additionally, the possibility of reversal of negative effects following withdrawal of treatment was examined. Fifty male rats (180 -200g body weight) were grouped into five (n = 10), namely: control, sildenafil, tadalafil, tramadol and sildenafil+tramadol group. The different groups were orally treated with 0.2mL normal saline, sildenafil (1 mg/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
(12 reference statements)
3
5
0
Order By: Relevance
“…These results are in agreement with each 15 and Owoade et al, 2019. The reason may be that the decrease in these blood components, due to the inhibitory effect of tramadol on the morphological differentiation of red blood cells, will affect the rest of the blood components, such as hemoglobin concentration and platelet count.…”
Section: Effect Of Tramadol On Hb Concentration Plt and Rbc Numberssupporting
confidence: 93%
See 4 more Smart Citations
“…These results are in agreement with each 15 and Owoade et al, 2019. The reason may be that the decrease in these blood components, due to the inhibitory effect of tramadol on the morphological differentiation of red blood cells, will affect the rest of the blood components, such as hemoglobin concentration and platelet count.…”
Section: Effect Of Tramadol On Hb Concentration Plt and Rbc Numberssupporting
confidence: 93%
“…Or it may be due to the adverse effect of the mechanism of blood clotting in the body. In addition, it causes the use of various analgesics such as tramadol, which many studies in this field 8,15,18,19,21 have confirmed.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations